Application of Islamic Counseling Approach in Handling Online Game Addiction - Muslima Muslima; Evi Zuhara; Yuliana Nelisma; Aulia Dian Miranda; Safira Khairun Nisa (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
The use of Islamic therapy to treat college students' addiction to internet gaming. Addiction to online gaming has become a major issue for college students, having a detrimental effect on their social lives, mental health, and academic performance. The purpose of this study is to investigate how well Islamic counseling works to treat college students' addiction to online gaming. Eight college students who had been diagnosed with an addiction to online gaming were among the 80 students in the quantitative-experimental sample employed in this study. An online gaming addiction scale that had undergone validity and reliability testing served as the tool. Data analysis employed an N-Gain test to observe changes in outcomes following the intervention, and a normality test to guarantee data distribution. Further analysis was made possible by the study's demonstration that the data were regularly distributed. After that, information was gathered via in-depth interviews to learn about the experiences of the participants and a questionnaire that assessed the degree of online gaming addiction before and after the intervention. The findings demonstrated that, in comparison to the control group, students who got Islamic therapy saw a notable drop in their degree of online gaming addiction. Additionally, participants felt that the counseling improved their social interactions and enhanced their spiritual well-being. These results suggest that by bolstering spiritual elements as a basis for recovery, Islamic counseling can be a successful and comprehensive approach to treating college students' addiction to online gaming. Thus, by helping students internalize spiritual ideals, cultivate self-control, and adopt healthy habits, an Islamic counseling method can effectively assist them lessen their addiction to online gaming.